2011
DOI: 10.1007/s10157-011-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of small doses of furosemide in chronic kidney disease patients with residual renal function undergoing hemodialysis

Abstract: The results of this study have shown that chronic use of small doses of furosemide in chronic renal patients with residual diuresis could increase urinary volume and sodium excretion compared to patients who did not use this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Given the risk of ototoxicity, use of diuretics in anuric patients on dialysis is not recommended (4,5). These compounds may have a role in those with preserved residual renal function as a maneuver to limit interdialytic weight gain (19); whether such an approach is useful or detrimental has not been adequately examined.…”
Section: Pharmacologic Management Of Hypertension In Patients On Dialmentioning
confidence: 99%
“…Given the risk of ototoxicity, use of diuretics in anuric patients on dialysis is not recommended (4,5). These compounds may have a role in those with preserved residual renal function as a maneuver to limit interdialytic weight gain (19); whether such an approach is useful or detrimental has not been adequately examined.…”
Section: Pharmacologic Management Of Hypertension In Patients On Dialmentioning
confidence: 99%
“…Medication classes for blood pressure management in dialysis Fosinopril did not reduce cardiovascular events and death compared with placebo in patients on HD with left ventricular hypertrophy 44 RCT: Inconsistent results related to ARBs and cardiovascular outcomes[45][46][47][48] Meta-analysis: ACEis/ARBs may reduce left ventricular mass index49 RCT: May preserve residual kidney function, especially in PD patients50,51 b-blockers RCT: Fewer heart failure hospitalizations with the b-blocker atenolol compared to the ACEi lisinopril in HD patients with hypertension and left ventricular hypertrophy 52 RCT: Lower risk of death and cardiovascular death with carvedilol versus placebo in HD patients with dilated cardiomyopathy who were also receiving digoxin and ACEi or ARB 53 Calcium channel blockers RCT: Amlodipine reduced cardiovascular events compared with placebo in HD patients with hypertension54 DiureticsProspective: May help preserve residual diuresis and limit fluid overload55,56 Prospective: Minimal effect on central hemodynamic indices and should not be considered an antihypertensive medication in the setting of dialysis57 Observational: Continuation of loop diuretics after HD initiation is associated with lower IDWG and lower intradialytic hypotension and hospitalization rates 58 Mineralocorticoid receptor antagonists RCT: Some trials in patients on dialysis have shown benefit on cardiovascular outcomes with spironolactone vs. placebo, 59-61 whereas others have not62 Ongoing RCTs: spironolactone and cardiovascular outcomes in HD patients (ACHIEVE and ALCHEMIST)63 …”
mentioning
confidence: 99%
“…Some studies have shown that the use of loop diuretics help salt and volume control and may help maintain RRF in dialysis patients [20][21][22] . DOPPS data from 3 continents, from nearly a decade ago, showed a wide variation in the use of diuretics from country to country ranging from 9% in the United States to 21% in Europe within the first 90 days of starting HD [22] .…”
Section: Discussionmentioning
confidence: 99%